Experimental Study of Performance and Emission Characteristics of Honge Oil with Waste Edible Biodiesel Blends - C S Srinivasa; B H Maruthi Prashanth; S Ramesh; Mahammadsalman Warimani; Noor Alam (International Journal of Integrated Engineering, 2025)
Due to the continuous increase in demand for fossil fuels and emissions of harmful gases, researchers are moving to form biodiesel from biomass with the same thermo-physical properties as pure diesel, lowering combustion exhaust emissions. In the present research work, the transesterification process uses an alkaline catalyst to form second-generation biodiesel from honge seeds and waste edible oil (WEO). The experimental tests are conducted by considering different concentration ratios of honge and Waste edible oil blended biodiesel such as 5H+10W+85D (H stands for 5% honge oil, W stands for 10% WEO oil, and D stands for 85% Diesel), 5H+20W+75D, 10H+5W+85D and 20H+5W+75D, and compared with pure diesel (D100) and bio-oil fuel (H100 & W100). The performance and emissions combustion parameters were measured at five loading conditions: 10%, 30%, 50%, 70%, and 100%. The novelty of the present research is that the blended fuel 5H+10W+85D exhibited a minimum BSFC of 0.23kg/kW-hr with a maximum brake thermal efficiency of 35.99% at a compression ratio of 16.5:1. The CO and HC emissions were also reduced for the biodiesel, but NOx emission is found to be increased.